HUBUNGAN ANTARA BERAT PLASENTA IBU PREEKLAMPSIA DENGAN BERAT BAYI LAHIR DI RSUD dr. DORIS SYLVANUS KOTA PALANGKA RAYA TAHUN 2019 - Lika Hanifah; Sigit Nurfianto; Ni Nyoman Sri Yuliani (Jurnal Kedokteran Universitas Palangka Raya, 2020)
Preeclampsia is one of the leading causes of maternal death. In preeclampsia occurs abnormalities of maternal placental blood vessels that cause chronic hypoxia and fetal nutritional disorders that affect the weight of the baby born. The aim of this study was to find out the correlation between placental weight of preeclampsia mothers with the baby born weight at RSUD dr. Doris Sylvanus Palangka Raya City in 2019. This study uses an analytic observational research design with a cross-sectional approach. The sample used was 35 placenta samples from preeclampsia mothers who gave birth at RSUD dr. Doris Sylvanus Palangka Raya taken by consecutive sampling technique. The results showed that mean of placental weight in preeclampsia mothers was 499.4 grams (SD = 146,685) an mean of baby born weight was 2,652.43 grams (SD = 481.341). Based on the analysis of Pearson correlation test results of placental weight of preeclampsia mothers have a correlation with the weight of babies born at RSUD dr. Doris Sylvanus City of Palangka Raya in 2019 with p < 0,001 and r = 0.679. The weight of the placenta in preeclampsia mothers has a significant correlation with the weight of babies born at RSUD dr. Doris Sylvanus Palangkaraya City 2019 with the strong level of correlation.